SOSIALISASI PELAKSANAAN RETENSI DAN PEMUSNAHAN REKAM MEDIS DI RS AWAL BROS BATAM - Ernaman Putri, Riza Suci; Putri, Widya; Wulandari, Siti (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2023)
Medical record is a file that contains notes or documents regarding patient identity, examinations, actions, and other services that have been provided to patients. Medical records are said to be of good quality if they are accurate, complete, reliable, valid and timely to return. According to the standard procedure (Protap) regarding the return of medical records no later than 2x24 hours after the patient returns home or after the patient leaves the hospital. This is intended so that medical record officers are ready to provide patient medical records if needed at any time. Awal Bros Batam Hospital has carried out retentions starting from 2016 onwards with vendors. Currently Awal Bros Batam Hospital already has 1 tool for destroying medical record files in the medical record unit. However, the lack of human resources in the medical record unit makes employees in medical records still doing work, not just one job but they do more than one job.